2019
DOI: 10.1016/j.ymthe.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a Promotes Renal Fibrosis by Downregulation of Klotho in Tubular Epithelial Cells

Abstract: Renal fibrosis is the main pathological characteristic of chronic kidney disease (CKD), whereas the underlying mechanisms of renal fibrosis are not clear yet. Herein, we found an increased expression of microRNA-34a (miR-34a) in renal tubular epithelial cells of patients with renal fibrosis and mice undergoing unilateral ureteral obstruction (UUO). In miR-34a À/À mice, miR-34a deficiency attenuated the progression of renal fibrosis following UUO surgery. The miR-34a overexpression promoted epithelial-to-mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 61 publications
0
85
0
Order By: Relevance
“…So far, there has been no study to report that dihydromyricetin exerts the anti-tumor effect by modulating miRNA. However, recent studies by Yang et al found that dihydromyricietin administration significantly restored the abnormal upregulation of miR-34a and ameliorated renal fibrosis in model mice [27]. Moreover, our previous study has shown that dihydromyricetin attenuates TNF-alpha-induced endothelial dysfunction through regulating miR-21 in HUVEC cells [10].…”
Section: Discussionmentioning
confidence: 89%
“…So far, there has been no study to report that dihydromyricetin exerts the anti-tumor effect by modulating miRNA. However, recent studies by Yang et al found that dihydromyricietin administration significantly restored the abnormal upregulation of miR-34a and ameliorated renal fibrosis in model mice [27]. Moreover, our previous study has shown that dihydromyricetin attenuates TNF-alpha-induced endothelial dysfunction through regulating miR-21 in HUVEC cells [10].…”
Section: Discussionmentioning
confidence: 89%
“…During the past few years, many studies have shown that the expression levels of miRNAs and their downstream target genes are closely associated with the progression of RF [3,4,2,10]. After applying various bioinformatics technologies as shown above, we found that Ptch1 is the most promising target mRNA of miR-342-5p in RF.…”
Section: Discussionmentioning
confidence: 76%
“…MicroRNAs (miRNAs) are endogenous small non-coding 21-25 nucleotide singlestranded RNAs s. miRNAs regulate gene expression by promoting the degradation of mRNAs or inhibiting the translation of mRNAs. miRNAs are involved in the development of various diseases, and several miRNAs are closely associated with RF, including miR-184, miR-34a, and miR-199a-3p [2][3][4]. Our review showed the recent progress, biological functions, and clinical applications of miRNAs in the progression of RF [5].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, both miR132-3p and miR214 have been found to be upregulated in various models of kidney diseases and associated with inflammation, apoptosis, myofibroblast activation, and dysregulation of the extracellular matrix (Denby et al, 2011(Denby et al, , 2014Bijkerk et al, 2016). Furthermore, attenuation of these miRNAs through inhibition or silencing has been shown to ameliorate the various forms of kidney diseases by downregulating pathways and processes favoring the progression of injury and fibrosis (Denby et al, 2011;Liu et al, 2019). Bioinformatic meta-analysis was performed on the predicted and validated target genes of these 7 miRNAs for the relative pathways to be identified.…”
Section: Discussionmentioning
confidence: 99%